The complete 1/N expansion of a SYK-like tensor model - Gurǎu, Rǎzvan (Nuclear physics. B, Particle physics, 2017)
A SYK-like model close to the colored tensor models has recently been proposed [1]. Building on results obtained in tensor models [2], we discuss the complete 1/N expansion of the model. We detail the two and four point functions at leading order. The leading order two point function is a sum over melonic graphs, and the leading order relevant four point functions are sums over dressed ladder diagrams. We then show that any order in the 1/N series of the two point function can be written solely in term of the leading order two and four point functions. The full 1/N expansion of arbitrary correlations can be obtained by similar methods.